Data‐Driven Transfer Functions From Differential Magnetometer Measurements to Enhance GIC Model Validation Capability: A Case Study in the Spanish Power Grid - S. Marsal; J. M. Torta; A. Martí; R. Hafizi; P. Piña‐Varas; A. Marcuello; J. Ledo; J. J. Curto; P. Queralt; O. Cid; M. Ibañez (Space Weather, 2025)
Abstract Geomagnetically induced currents (GICs) are unwanted currents flowing in long grounded conductors because of space weather phenomena. Example GICs are those flowing in power transmission lines via grounded transformer neutrals. Prediction models, used to foresee the amplitudes and waveforms of those currents and to identify weak points in those utilities, depend on the power grid parameters and on the ground resistivity. The differential magnetometer method (DMM), based on dual magnetic measurements, one under a power line and the other at a reference location a few hundred meters away, is used to locally validate those models by indirectly measuring the GIC. We first update our validation results at our DMM stations in Spain using the Earth Resistivity Model of the Iberian Lithosphere and discuss its performance. Second, we propose the use of geomagnetic interstation transfer functions to reproduce the magnetic measurements at the DMM reference location from geomagnetic observatory data, thus reducing the number of field instruments and saving on its maintenance.